Analysis of the Success of ICT at the Ikageng MPCC in Support of the Itsoseng Community: A Case Study - Jacobs, SJ; Herselman, Marlien (LINK Centre, University of the Witwatersrand (Wits), Johannesburg, 2004)
Information and communication technology is changing every facet of our lives, and thus changing how we live. This in turn impacts on the way we utilise information and communication technology in multi-purpose community centres, which provide support services to the communities in which they are located. A case study was conducted at the information and communication technologyequipped Ikageng Multi-purpose Community Centre in Itsoseng, situated in the North West Province of South Africa, to investigate the services delivered; the Centre utilises information and communication technology infrastructure to deliver needed services to the community. The lack of ongoing and sustained training for Centre staff, as well as the challenge of maintaining the Centre’s equipment, were some of the shortcomings identified by the study in terms of service delivery